Toxicological Findings in Fatal Road Traffic Accidents in Cape Town: A Pilot Study - Shongwe, Nondumiso Khetsiwe Ntombi (Division of Forensic Medicine and Toxicology, 2020)
Introduction: Road traffic accidents (RTAs) and associated morbidity and mortality are a global public health burden. Literature reports on an association between drugs and/or alcohol intoxication and traffic collisions. In South Africa (SA), where drug use and abuse are prevalent, annual RTAs rates are higher than the average global burden. Toxicological analyses in cases of RTA fatalities are not performed routinely in SA (apart from alcohol analysis), thus understanding the burden of other drug impairment on road traffic deaths is limited. Aim: A prospective toxicological analysis was performed in a cohort of road traffic fatality cases (drivers, passengers, pedestrians, motorcyclists and cyclists) from Salt River Mortuary in Cape Town, SA. The objectives were to perform drug screening in these cases to preliminary investigate detected substances as well as to evaluate the demographics and circumstances of death of the aforementioned cases. Methods: A systematic review was first performed to investigate the prevalence of drugs in internationally reported RTA fatalities. For the prospective study, post-mortem specimens including blood, vitreous humor, urine and bile were collected from cases in which next-of-kin consent was obtained. All samples were analysed using liquid chromatography-quadrupole time-of -flight mass spectrometry (LC/QTOF-MS). Results: Thirty cases were analysed over 3 months, of which most were male, pedestrians and between the age group of 31-40 years. The most prevalent cause of death was multiple blunt force injuries to the body. Single vehicle crashes were predominant particularly among the pedestrians and motorcyclists whereas drivers were mostly involved in multiple vehicle crashes. Substances (other than ethanol) were detected in 90% (n=27) of the cases. A broad range of drug groups were detected, and the most prevalent specific legal substances were caffeine (66.7%) and nicotinamide (53.3%) and illegal substances were methaqualone (10.0%) and methamphetamine (6.67%). Multiple cases indicated the detection of impairing substances even if consumed therapeutically, such as codeine, chlorpheniramine, diphenhydramine and zopiclone. Discussion: This study was the first to the author’s knowledge to report on prospective toxicological findings in road traffic accident cases in Cape Town. Although this was a pilot study, the results were in line with findings from other international studies, together with findings of prominent abused drugs within Western Cape (e.g. methaqualone and methamphetamine). While this study made no inferences of drug intoxication to cause of death, it has set a basis for future research in this topic and the development of a standardised protocol for the routine analyses of such cases in SA.